A midnight dance - Politano, Joanna Davidson, 1982- (Revell, a division of Baker Publishing Group, 2021)
"As Ella strives to keep her place in a struggling ballet company, the tragic story of another dancer seems to haunt her every step. If Ella can discover the truth of what happened, perhaps she can be free of the story and learn how to dance and live with the freedom that makes her story her own"--